2018
DOI: 10.1080/10942912.2018.1502199
|View full text |Cite
|
Sign up to set email alerts
|

Development of a predictive model to determine potato flour content in potato-wheat blended powders using near-infrared spectroscopy

Abstract: Potato is a good source of dietary energy and several micronutrients, and the development of staple foods using potato-wheat blended powder has received much attention recently in China. A rapid and accurate method for determining the potato flour content in potato staple foods would be valuable to market regulation efforts. We developed a predictive model for the potato flour content in potato-wheat blended powders based on near-infrared spectroscopy (NIRS) analysis. The correction of the near-infrared optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…From this study, it was observed that NIRS as a low‐cost technique could be adapted to quality control schemes for screening many samples with high accuracy. Relatively similar studies have been undertaken for taro (Lebot et al ., 2011a, 2011b), potatoes (Huang et al ., 2018), sweet potato (Lu et al ., 2006) and even for root and tuber crop‐based flour blended with cereal flour (Huang et al ., 2018) or consumptive products such as bread (Wang et al ., 2019). Su & Sun (2017) explored Spectral imaging for quantitative detection of Irish organic wheat flour adulterated with cassava flour and cornflour.…”
Section: Nirs and Hsi Techniques For High‐throughput Phenotyping For mentioning
confidence: 99%
“…From this study, it was observed that NIRS as a low‐cost technique could be adapted to quality control schemes for screening many samples with high accuracy. Relatively similar studies have been undertaken for taro (Lebot et al ., 2011a, 2011b), potatoes (Huang et al ., 2018), sweet potato (Lu et al ., 2006) and even for root and tuber crop‐based flour blended with cereal flour (Huang et al ., 2018) or consumptive products such as bread (Wang et al ., 2019). Su & Sun (2017) explored Spectral imaging for quantitative detection of Irish organic wheat flour adulterated with cassava flour and cornflour.…”
Section: Nirs and Hsi Techniques For High‐throughput Phenotyping For mentioning
confidence: 99%
“…In this regard, near infrared reflectance (NIR) spectroscopy has become a widely used method of quality control in the food processing industry. 28,29 It is a rapid, cost-effective and non-destructive technique allowing the simultaneous determination of major chemical constituents. NIR spectroscopy has been used to predict the content of major constituents in sweet potato, cassava, yam and taro crops.…”
Section: Introductionmentioning
confidence: 99%
“…Models of NIRS have been developed for the rapid characterisation of essential quality traits in various Dioscorea spp. [12,14,15] and have been successfully applied in many crops, including potato, cassava, and sweet potato [16][17][18][19]. Quantification of dry matter and protein in yam bean using NIRS was reported with an excellent prediction performance of 0.94 and a SEP of 1.2 [20].…”
Section: Introductionmentioning
confidence: 99%